Language proficiency and diversity in students’ attitudes towards code-switching: a case study of English as a foreign language classrooms in Italian tertiary education - Antonella Luporini; Antonella Giacosa; Cristiano Furiassi (Revista de Lingüística y Lenguas Aplicadas)
By relying on a mixed-method approach consisting of a combination of various quantitative and qualitative techniques of data collection and processing, this article delves into the attitudes towards code switching (CS), as expressed by students attending English language and English linguistics courses at two Italian universities. Data are retrieved by means of a questionnaire, submitted to 297 students in total and including both closed- and open-ended questions. Based on concepts such as those of conversational loci, or CS functions – namely academic, managerial and social, all well-rooted in the literature – this article also aims at establishing a link between students’ attitudes and their respective proficiency level in English according to the CEFR. Despite managing to establish that teacher CS is not felt to have a negative impact on their language skills, the data gathered reveal diverse attitudes, also in relation to the specific functions examined. In the conclusion, possible pedagogical implications of classroom CS are proposed and assessed.